Occurrence and characterization of NDM-5-producing Escherichia coli from retail eggs - Liu, Yi-Yun; Li, Tong; Yue, Huiying; Yue, Chao; Lu, Litao; Chen, Junqiang; Deng, Haotian; Gao, Xun; Liu, Jian-Hua (Frontiers in Microbiology, 2023)
The New Delhi Metallo-β-lactamase (NDM) producing Enterobacterales has been detected from diverse sources but has rarely been reported in retail eggs. In this study, a total of 144 eggshell and 96 egg content samples were collected in 2022 from Guangdong province and were screened for NDM-producing strains. Four Escherichia coli (ST3014, ST10, ST1485 and ST14747) strains recovered from two (1.39%, 2/144) eggshell and two (2.08%, 2/96) egg content samples were identified as blaNDM-5positive strains. Oxford Nanopore MinION sequencing and conjugation assays revealed that the blaNDM-5 gene were carried by IncX3 (n=1), IncI1 (n=1), and IncHI2 (n=2), respectively. The IncI1-plasmid carrying blaNDM-5 displayed high homology with one plasmid pEC6563-NDM5 from human clinic, while the IncHI2 plasmid harboring blaNDM-5 shared highly similar structures with plasmids of animal origin. To the best of our knowledge, this is the first report on the identification of blaNDM-5-positive bacteria in retail eggs. NDM-producing E. coli could be transmitted to the human by consumption of eggs or direct contact, which could pose a potential threat to human health.